Knowing about and Performing Professionalism: Developing Professionalism in Interprofessional Healthcare Education - Mason, Rosemarie; Vitkovitch, Jennie; Lambert, Rod; Jepson, Jill (International Journal of Practice-based Learning in Health and Social Care, 2016)
Professionalism, and the ways in which it can be developed and maintained, has a high profile in today's health and social care climate. It is becoming increasingly important that higher education institutions develop ways of making teaching about the concept explicit; yet, teaching professionalism can be challenging for a number of reasons. Constructs of professionalism frequently represent character traits and attitudes rather than behaviours, which by definition makes them difficult to teach and potentially problematic to learn. Students of the School of Rehabilitation Sciences (RSC) within the University of East Anglia (UEA) have been using a Professionalism Charter since 2011. The purpose of the charter is to define the construct of professionalism for RSC students, to provide a tangible framework around which professionalism can be structured, to enable students to map changes in their professional attitudes, behaviours, knowledge and skills and to highlight areas for development. Evaluation of the charter has demonstrated that it is helpful in providing a reference point for best practice. Refinements are necessary, but the indications are that it has the potential to facilitate students' understanding of (knowing about) professionalism and provides them with opportunities to actively engage (perform) in practice.